Towards Feature-Free Automated Algorithm Selection for Single-Objective Continuous Black-Box Optimization - Prager, Raphael Patrick; Vinzent Seiler, Moritz; Trautmann, Heike; Kerschke, Pascal (2021 IEEE Symposium Series on Computational Intelligence (SSCI))
We propose a novel method for automated algorithm selection in the domain of single-objective continuous black-box optimization. In contrast to existing methods, we use convolutional neural networks as the selection apparatus which bases its decision on a so-called ‘fitness map’. This fitness map is a 2D representation of a two dimensional search space where different gray scales indicate the quality of found solutions in certain areas. Our devised approach uses a modular CMA-ES framework which offers the option to create the conventional CMA-ES, CMA-ES with the alternate step-size adaptation and many other variants proposed over the years. In total, 4 608 different configurations are possible where most configurations are of complementary nature. In this proof-of-concept work, we consider a subset of 32 possible configurations. The developed method is evaluated against an excerpt of BBOB functions and its performance is compared against baselines that are commonly used in automated algorithm selection - the best standalone algorithm (configuration) and the best obtainable sequence of configurations. While the results indicate that the use of the fitness map is not superior on every benchmark problem, it indubitably shows its merit on more hard-to-solve problems. This offers a promising perspective for generalizing to other types of optimization problems and problem domains.

RP-Mod & RP-Crowd: Moderator- and Crowd-Annotated German News Comment Datasets - Assenmacher, Dennis; Niemann, Marco; Müller, Kilian; Seiler, Moritz V.; Riehle, Dennis M.; Trautmann, Heike (Proceedings of the Neural Information Processing Systems Track on Datasets and Benchmarks 1 (NeurIPS Datasets and Benchmarks 2021))
Abuse and hate are penetrating social media and many comment sections of news media companies. These platform providers invest considerable efforts to mod- erate user-generated contributions to prevent losing readers who get appalled by inappropriate texts. This is further enforced by legislative actions, which make non-clearance of these comments a punishable action. While (semi-)automated solutions using Natural Language Processing and advanced Machine Learning techniques are getting increasingly sophisticated, the domain of abusive language detection still struggles as large non-English and well-curated datasets are scarce or not publicly available. With this work, we publish and analyse the largest annotated German abusive language comment datasets to date. In contrast to existing datasets, we achieve a high labelling standard by conducting a thorough crowd-based an- notation study that complements professional moderators’ decisions, which are also included in the dataset. We compare and cross-evaluate the performance of baseline algorithms and state-of-the-art transformer-based language models, which are fine-tuned on our datasets and an existing alternative, showing the usefulness for the community.

Gender and Authority – The Entanglement of Two Concepts in High Medieval Historiography - Foerster, Anne (Geschlecht macht Herrschaft – Interdisziplinäre Studien zu vormoderner Macht und Herrschaft / Gender Power Sovereignty – Interdisciplinary Studies on Premodern Power)

Die Witwenschaft kinderloser Königinnen im Hochmittelalter - Foerster, Anne (Kinderlosigkeit im Mittelalter)

Erklärvideos in der Sprachwissenschaft – Sprache-Bild-Bezüge und ihr Einfluss auf den Lernerfolg (die hochschullehre – Jahrgang 7-2021)

A Database for Research on Detection and Enhancement of Speech Transmitted over HF links - Heitkaemper, Jens; Schmalenstroeer, Joerg; Ion, Valentin; Haeb-Umbach, Reinhold (Speech Communication; 14th ITG-Symposium)

How entrepreneur’s leadership behavior and demographics shape applicant attraction to new ventures: the role of stereotypes - Hubner-Benz, Sylvia; Rudic, Biljana; Baum, Matthias (The International Journal of Human Resource Management)
Keywords: Management of Technology and Innovation; Organizational Behavior and Human Resource Management; Strategy and Management; Business and International Management; Industrial relations

An Asia-centric approach to team innovation: Cultural differences in exploration and exploitation behavior - Hubner-Benz, Sylvia; Frese, Michael; Song, Zhaoli; Tripathi, Neha; Kaschner, Tamara; Le Kong, Xing (Journal of Business Research)
Keywords: Marketing

Introduction - Jacob, Joachim; Süßmann, Johannes (The Reception of Antiquity in the Age of Enlightenment. English Edition ed. by Christina C. Harker. Translated by Duncan Alexander Smart)

Investigating students' processes of noticing and interpreting syntactic language features in word problem solving through eye-tracking - Dröse, Jennifer; Prediger, S.; Neugebauer, P.; Danhier, R. D.; Mertins, B. (International Electronic Journal of Mathematics Education, 16(1), em0625)